HPV16 E6 promotes cervical cancer cell migration and invasion by downregulation of NHERF1. Issue 7 (13th December 2018) - Wang, Qiqi; Song, Ran; Zhao, Chunjuan; Liu, Hua; Yang, Ying; Gu, Siyu; Feng, Duiping; He, Junqi
Abstract : HPV16 is the predominant type of HPV causing invasive cervical cancer. However, the underlying molecular mechanism of the unparalleled carcinogenic power of HPV16 compared to other types of high‐risk (HR)‐HPV including HPV18 remains elusive. The PDZ binding motif (PBM) of high‐risk HPV E6 plays an important role in neoplasia and progression of cervical cancer. HPV16 E6 rather than HPV18 E6, interacted with NHERF1 by its PBM region, and induced degradation of NHERF1. NHERF1 retarded the assembly of cytoskeleton by downregulation of ACTN4, thereby inhibited the migration and invasion of cervical cancer cells in both cell and mouse model. HPV16 E6 was confirmed to enhance actin polymerization with increased ACTN4 level by downregulation of NHERF1, and result in enhanced migration and invasion of cervical cancer cells. GSEA analysis of cervical cancer specimens also showed that HPV16 E6 rather than HPV18 E6, was significantly associated with actin cytoskeleton assembly. That downregulation of NHERF1 by HPV16 E6 promoted cytoskeleton assembly and cell invasion, was an important cause in cervical cancer carcinogenesis. These findings provided the differential mechanism between HPV16 E6 and HPV18 E6 in the development and progression of cervical cancer, which may partially explain the differences of carcinogenic power between these two types of HR‐HPVs. Abstract : What's new? Human papillomavirus 16 (HPV16) causes about 46–63% of invasive cervical cancers (ICCs) worldwide. The mechanisms underlying its carcinogenicity remain unknown. Our study shows that the PDZ‐binding motif of HPV E6 proteins, is required for HPV16 E6‐promoted cervical cell migration and invasion. HPV16 E6 interacted with the PDZ domain‐containing protein Na + /H + exchanger regulatory factor 1 (NHERF1), downregulating its expression and thereby increasing levels of the actin cytoskeleton protein ACTN4 and facilitating cell migration and invasion. By contrast, the E6 proteins of HPV18, which causes 10–15% of ICCs, did not downregulate NHERF1, indicating that HPV16 E6 and HPV18 E6 act via different carcinogenic mechanisms.